1992
DOI: 10.2118/22800-pa
|View full text |Cite
|
Sign up to set email alerts
|

New Continuous-Mix Process for Gelling Anhydrous Methanol Minimizes Hazards

Abstract: Summary This paper discusses a novel approach to well stimulation with anhydrous methanol-based fracturing-fluid that significantly reduces hazards to personnel and equipment during the fracturing process. Research is presented on the various chemical and engineering process technologies used to develop and evaluate continuously mixed anhydrous methanol fracturing-fluid performance. Field case histories are also discussed. Introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Water-based fluids are the most common ones and contain several chemicals, although at low concentrations . According to the U.S. House Energy and Commerce Committee “Chemicals Used in Hydraulic Fracturing” report, methanol is the most widely used additive , in small fractions of the total fluid volume, playing a diverse role in corrosion or scale inhibition, friction reduction, formation water flowback enhancement, and fracking fluid flowback enhancement. ,, Another additive is citric acid, , which is used primarily to prevent the release of ferric iron, a problematic factor in fracturing. Apart from the presence of chemicals, fracturing fluids returning to the surface have been found to contain elevated levels of strontium (Sr 2+ ), sodium (Na + ), and chloride (Cl – ) ions, as well as naturally occurring radioactive materials (NORM) such as radium (Ra 2+ ) isotopes. …”
Section: Introductionmentioning
confidence: 99%
“…Water-based fluids are the most common ones and contain several chemicals, although at low concentrations . According to the U.S. House Energy and Commerce Committee “Chemicals Used in Hydraulic Fracturing” report, methanol is the most widely used additive , in small fractions of the total fluid volume, playing a diverse role in corrosion or scale inhibition, friction reduction, formation water flowback enhancement, and fracking fluid flowback enhancement. ,, Another additive is citric acid, , which is used primarily to prevent the release of ferric iron, a problematic factor in fracturing. Apart from the presence of chemicals, fracturing fluids returning to the surface have been found to contain elevated levels of strontium (Sr 2+ ), sodium (Na + ), and chloride (Cl – ) ions, as well as naturally occurring radioactive materials (NORM) such as radium (Ra 2+ ) isotopes. …”
Section: Introductionmentioning
confidence: 99%
“…Crosslinked gels have been employed to facilitate proppant transport by increasing the viscosity of non-aqueous fluids during fracturing. Laboratory studies and field application of crosslinked gelled methanol-based fracturing fluid demonstrated higher regained permeability than crosslinked water-based gel and gelled oil (Thompson et al 1992). Miscibility in water and favorable interfacial tension help achieve more efficient clean up and recovery of the flow back after fracturing treatment, thus increasing the permeability to the gas phase from matrix to fracture networks.…”
Section: Gelled Alcohol and Lpg Systemsmentioning
confidence: 99%
“…Three concerns with methanol all relate to safety: low flash point, high vapor density and flame invisibility. With special precautions, as previous authors have identified (3,5) methanol can be safely used in the field.…”
Section: Introductionmentioning
confidence: 95%